If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(a+2)=-5-2 (a-3)
We simplify the equation to the form, which is simple to understand
3(a+2)=-5-2(a-3)
Reorder the terms in parentheses
+(+3a+6)=-5-2*(a-3)
Remove unnecessary parentheses
+3a+6=-5-2+*(+a-3+)
Reorder the terms in parentheses
+3a+6=-5+(-2a+6)
Remove unnecessary parentheses
+3a+6=-5-2a+6
We move all terms containing a to the left and all other terms to the right.
+3a+2a=-5+6-6
We simplify left and right side of the equation.
+5a=-5
We divide both sides of the equation by 5 to get a.
a=-1
| w/7+9=-3 | | -3(3d-2)=4-d | | 12+5x=2x-11 | | 2x+x^2=224 | | 25=-n/6+(-19) | | 6(a-7)+10=4(a-7) | | 4(5-m)=3(3-2m) | | -8-(y+7)=-6y | | 22y=63 | | x^2+1+3x+6+x=180 | | 4r=2(r-5)-2 | | (x^2+6)(x^5-3x^3-54x)=0 | | 24.75+6x=31.2+3x | | 4-7m=1-6m | | 1.25a=1.222 | | -3=-7t | | 4(x+6)-4=6(x+3)-6 | | 6y-5=7y | | 4x-6=x+49 | | 1.25a=1.22 | | 2x^2+89=-4 | | 1.25a=1.22222 | | 66w-37-23w=49 | | 52c-14-35c=133 | | 0.065(x+2000)=0.07x+0.04(1000) | | 5-(a+3)=2a+6-3a | | 7p+6p= | | 10x+6y=97.5 | | x-4=2(2x-5) | | 10x+3=7x+4 | | 7n-n+12= | | 2x=3x+29 |